Burning Mouth Syndrome Following Covid Vaccination: A Case Report - Mustafa Broachwala; Dylan W. Banks; David S. Jevotovsky; Whitman Oehlermarx; Shravani Durbhakula (Clinical Case Reports)
ABSTRACT This is the first reported case of burning mouth syndrome resulting from the Pfizer‐BioNTech COVID‐19 vaccine. It highlights the efficacy of a unique multimodal treatment regimen, including zinc supplementation, acupuncture, and topical capsaicin.